The role and efficacy of management in influencing the implementation of an occupational health and safety policy : a case study of DaimlerChrysler South Africa East London - Pringle, Jessica Samantha (Rhodes University, Faculty of Humanities, Department of Sociology, 2007)
The existence of an occupational health and safety policy is believed to be evidence of management accepting their occupational health and safety role in terms of the Occupational Health and Safety Act. It is accepted that this results in management ensuring the provision of a safe workplace. Despite the emphasis in legislation (the Occupational Health and Safety Act) on the need for management to implement comprehensive occupational health and safety policies, there is a lack of research on the implementation and efficacy of occupational health and safety policies in the workplace. This study investigates the efficacy with which management carries out their occupational health and safety duties and responsibilities when implementing the provisions of an occupational health and safety policy in the workplace. A number of factors are essential to the efficient performance of management in this regard. These factors include managerial commitment, practices and strategies; communication practices and structures; training initiatives and information; the extent of employee and trade union involvement; and the infrastructure of the organisation. This research study is primarily qualitative in nature. Semi-structured interviews were the primary tool used by the researcher to collect the data. The case-study research method was employed to assist the researcher in collecting the data. The participants involved in the research were selected using the principles of strategic informant sampling and expert choice sampling. The participants consisted of a sample of management, employees and shop stewards. The research findings indicate that firstly, the presence of occupational health and safety policies, practices, strategies and systems in the workplace do not automatically result in reduced hazards, accidents or deaths in the workplace. Secondly, the participation schemes and the communication practices put in place by management are weak. The reason for their weakness is their ineffective implementation by management and use by employees and the trade union. Thirdly, management has a definite impact on the involvement, attitudes and actions of the employees and the trade union in occupational health and safety issues. Fourthly, there is an unequal partnership between management and employees as a result of the educational differences regarding occupational health and safety between them. The outcome is that management and employees are faced with numerous challenges in relation to occupational health and safety. Contributing to this challenge is a lack of sufficient resources allocated to training, resulting ultimately in the ineffective monitoring of occupational health and safety in the workplace. The existence of occupational health and safety structures and systems does not provide the essential evidence to suggest that their mere presence makes a difference to the workplace safety level. However, through more co-operation and participation by all the parties, these structures and systems have the potential to be effective.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: DaimlerChrysler; Automobile industry and trade -- South Africa -- East London -- Case studies; Industrial safety -- Law and legislation -- South Africa; Industrial hygiene -- Law and legislation -- South Africa; Industrial safety -- Management -- South Africa; Industrial hygiene -- Management -- South Africa